Penetrasi Metaverse untuk Meningkatkan Pembelajaran dalam Pendidikan - Mustofa, Reyhan Diki; Abelia, Elsi; Sandi, Rangga Apri (Jurnal Kridatama Sains dan Teknologi, 2025)
This study aims to analyze the penetration of Metaverse technology in enhancing the quality of learning within the educational sector using a qualitative approach based on secondary data. Data were collected through documentation techniques, including a review of scholarly journals, research reports, policy documents, media articles, and case studies on the implementation of Metaverse in educational settings. The analysis was conducted descriptively, focusing on how Metaverse technology has been adopted, the outcomes it has generated, and the challenges and opportunities that accompany its integration into learning processes. The findings reveal that the Metaverse has significant potential to enrich learning experiences through interactive simulations, collaborative avatar-based learning, and immersive educational environments. Various educational institutions worldwide have adopted Metaverse platforms, showing improvements in student engagement and conceptual understanding. However, issues such as technological access, educator readiness, and infrastructure limitations remain considerable barriers. This study provides a conceptual and contextual overview of the importance of strategic adoption to ensure that the use of Metaverse in education can be optimized and made inclusive.